High serum C-reactive protein level predicts mortality in patients with stage 3 chronic kidney disease or higher and diabetic foot infections - Sang Jin Lee; Yoon Chul Jung; Dong Ok Jeon; Hyo Jin Cho; Sung Gyu Im; Sun Kyung Jang; Ho Joon Kang; Mi Jung Kim; Jang Han Lee (The Korean Society of Nephrology, 2013)
Background: Diabetic patients are predisposed to foot infections because of vascular insufficiency and peripheral neuropathy. Diabetic foot infection is a common cause of mortality and lower extremity amputations (LEAs) in patients with chronic kidney disease (CKD). We evaluated the risk factors for mortality and LEAs in patients with stage 3 CKD or higher with diabetic foot infections. Methods: We retrospectively evaluated a cohort of 105 CKD patients with diabetic foot infections between July 1998 and December 2011. We reviewed their demographic characteristics and laboratory parameters to evaluate the risk factors for mortality and amputations at 24 weeks after diagnosis of a diabetic foot infection. Results: The mortality of the 105 enrolled CKD patients was 21% at 24 weeks after the diagnosis of a diabetic foot infection. Cox proportional regression analyses revealed that age 60 years or older [odds ratio (OR) 3.03, 95% confidence interval (CI) = 1.02-9.02, P = 0.047] and initial serum C-reactive protein (CRP) level ≥ 3 mg/dL (OR 3.97, 95% CI = 1.17-13.43, P = 0.027) were independent risk factors for mortality at 24 weeks. Twenty-four patients (23%) underwent LEAs. On Cox proportional regression analyses, peripheral vascular disease (OR=4.49, 95% CI=1.98-10.17, P=0.01) and cerebrovascular accident (OR 2.42, 95% CI=1.09-5.39, P=0.03) were independently associated with LEAs. Conclusion: This study showed that age and serum CRP level, were independent risk factors for mortality at 24 weeks in patients with stage 3-5 CKD with diabetic foot infections. Peripheral vascular disease and cerebrovascular accident were significantly associated with LEAs.